Development of the Interactive Learning in Traditional Games (ILinG) Model in the Game “Sluku-sluku Bathok” as a Tool for Meaningful Learning in the Society 5.0 Era - Nurdyansyah; Nur Maslihatun Nisak; Risky Nadhifah Azzahro; Pandi Rais (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and test the feasibility, practicality, and effectiveness of the Interactive Learning in Traditional Games (ILinG) model as a means of promoting meaningful learning in the Society 5.0 era. The study employed a Research and Development (R&D) method using the ADDIE framework, which consists of the analysis, design, development, implementation, and evaluation stages. The research was conducted in an elementary school in the Sidoarjo region. The sampling technique used was purposive sampling. Data were collected through questionnaires, document analysis, and tests, and were analyzed using mixed-methods techniques to obtain comprehensive findings. Based on expert validation results, the developed model demonstrated a very high level of feasibility. The material expert provided an average score of 3.74, categorized as “very feasible,” while the design expert assigned a score of 3.63, also categorized as “very feasible.” In addition, the linguistic validation obtained a score of 3.77, which likewise falls into the “very feasible” category. In terms of practicality, small-group testing (5 students) resulted in a score of 93.57%, while large-group testing (12 students) yielded 80.95%, indicating that the ILinG model is highly practical for classroom implementation. Regarding effectiveness, t-test analysis revealed a significant difference in mean scores between the control group (71.33) and the experimental group (89.21). The statistical test showed a significance value (p < 0.05), indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. These findings confirm that (1) the ILinG model has a significant positive effect on students’ meaningful learning, and (2) the model is highly effective as a learning intervention to enhance meaningful learning in the Society 5.0 era.